Proximal Capsular Augmentation With the Indirect Head of the Rectus Femoris for Longitudinal Capsulotomy in Primary Hip Arthroscopy - Shi-Yu Sha, M.S.; Tao Liang, M.S.; Yi Liu, M.D.; Quan-He Jin, M.D.; Wen-Guang Liu, M.D.; Qing-Feng Yin, M.D. (Arthroscopy Techniques)
The positive effect of the capsular closure in maintaining the integrity of the joint capsule has been demonstrated, but most capsular closure techniques are primarily for interportal capsulotomy, with few techniques described for longitudinal capsulotomy. In our clinical practice, the incomplete closure of the proximal capsule in longitudinal capsulotomy may result in weakness or nonunion of the proximal capsule. Thus, we propose a technique of anatomic repair of the joint capsule with the indirect head of the rectus femoris as proximal augmentation in cases of longitudinal capsulotomy. This technique could provide a plausible and feasible solution for complete capsular closure of the longitudinal capsulotomy, which could decrease the risk of weakness or nonunion of the proximal capsule.